From Green Identity to Green Intentions: Exploring Consumer Behavior among Undergraduates - Ghazali, Nur Aneesa; Abdul Hamid, Norhadilah (Research in Management of Technology and Business, 2025)
College students are widely regarded as key agents of social transformation; thus, their environmental knowledge is critical in addressing the risks posed by solid waste and other ecological challenges within their communities. Furthermore, students play a vital role in fostering sustainability and promoting ecological awareness. This study aims to examine the influence of green product awareness, green perceived price, green perceived availability, green perceived value, and green perceived quality on green purchase intentions among university students. A quantitative research design was employed, involving a survey of 370 undergraduate students. Data were analyzed using descriptive statistics, reliability analysis, normality testing, and correlation analysis with SPSS software. The findings revealed that all five factors green product awareness, green perceived price, green perceived availability, green perceived value, and green perceived quality positively influence green purchase intentions. Among these, green product awareness emerged as the most influential predictor, followed by green perceived price, green perceived value, green perceived quality, and green perceived availability.